Uji Potensi Tumbuhan Akumulator Merkuri untuk Fitoremediasi Lingkungan Tercemar Akibat Kegiatan Penambangan Emas Tanpa Izin (PETI) di Kampung Leuwi Bolang, Desa Bantar Karet, Kecamatan Nanggung, Bogor - Juhaeti, Titi; Hidayati, N.; Syarif, F.; Hidayat, S. (Perhimpunan Biologi Indonesia, 2009)
ABSTRACTThe research were carried out in Hg contaminated paddy field in Kampung Leuwibolang,Desa Bantar Karet, Kecamatan Nanggung, Kabupaten Bogor. The aim of this research is tostudy the potency of Salvinia molesta, Oryza sativa, Monocharia vaginalis, Limnoharisflava, Paspalum conjugatum, Cyperus monocephala, Centrosema pubescens, Mikania cordataand Commelina nudiflora to accumulate Hg from contaminated soil. The treatments werefertilizer: no fertilizer (as a control), NPK, manure and compost. The result showed that thegrowth of each plant was significantly different. The fertilizer treatments were significantlyaffected plant growth. The S. molesta showed the highest biomass followed by M. vaginalis,O. sativa and C. nudiflora. Meanwhile S. molesta also showed the highest capasity toaccumulate Hg/year followed by C. nudiflora, P. conjugatum dan M. vaginalis. Production ofbiomass and accumulation capasity of contaminant were the characteristic of accumulatorplant. Based on characteristic of hyperaccumulator plant, this research suggested that S.molesta, M. vaginalis, P. conjugatum, O. sativa dan C. nudiflora were selected forfitoremediation of Hg contaminated soil.Keywords: Accumulator plant, Hg, biomass, accumulation capacityKatakunci: Tumbuhan akumulator, Hg, biomas, kapasitas akumulasi